Respuesta :
Answer:
Simplifying
4x + -23 = 2x + 17
Reorder the terms:
-23 + 4x = 2x + 17
Reorder the terms:
-23 + 4x = 17 + 2x
Solving
-23 + 4x = 17 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
-23 + 4x + -2x = 17 + 2x + -2x
Combine like terms: 4x + -2x = 2x
-23 + 2x = 17 + 2x + -2x
Combine like terms: 2x + -2x = 0
-23 + 2x = 17 + 0
-23 + 2x = 17
Add '23' to each side of the equation.
-23 + 23 + 2x = 17 + 23
Combine like terms: -23 + 23 = 0
0 + 2x = 17 + 23
2x = 17 + 23
Combine like terms: 17 + 23 = 40
2x = 40
Divide each side by '2'.
x = 20
Simplifying
x = 20
Step-by-step explanation: